Research on single event effect test of a RRAM memory and space flight demonstration. (November 2021) - Lyu, He; Zhang, Hongwei; Mei, Bo; Yu, Qingkui; Mo, Rigen; Sun, Yi; Gao, Wu
Abstract: As a non-volatile memory, the resistive random access memory (RRAM) has some advantages in radiation tolerance and application prospects in space. RRAM has the advantages of high storage density, high repetition times and three-dimensional storage. This paper analyzed the working principle of RRAM, selected an RRAM memory as the research object, carries out the sensitivity test of heavy ion single event effect. The single event effect on orbit outage rate of the device was calculated by using the space on-orbit prediction software, ForeCAST. In addition, the natural anti-radiation performance of the storage area of the device was verified by pulsed laser induced test, and the good anti-radiation performance of the device was further verified by space flight test. Highlights: It presents a complete single event effect radiation characterization of an RRAM. The heavy ion radiation results of RRAM are given that resistive memories are SEU-immune but the peripheral CMOS is sensitive to SEFI. The single event effect on orbit outage rate of the device was given by using the space on-orbit prediction software, ForeCAST. The pulsed laser experiment on RRAM has been carried out to verify heavy ion radiation results of RRAM. The space flight experiment on RRAM has been carried out to verify SEFI rate in orbit prediction by ForeCAST and its good anti-radiation performance.